Abstract Number ‐ 187: Short‐term Clinical Outcomes Amongst Patients On Anticoagulation and DAPT Who Underwent Stenting and Mechanical Thrombectomy - Hamzah M Saei; Sohum Desai; Sherief Ghozy; Ermias Aytenfisu; Niti Dharwadkar; Ameer Hassan (Stroke: Vascular and Interventional Neurology, 2023)
Introduction Dual antiplatelet therapy has long been established as the preferred treatment option for patients with intracranial or extracranial stenting. Anticoagulation is the preferred treatment option for patients at high risk of stroke with embolic risk factors. There is no data currently available analyzing patients presenting with acute ischemic stroke on anticoagulation who require an intracranial and or extracranial stent (IC/EC), requiring DAPT and anticoagulation with mechanical thrombectomy. Our objective is toinvestigate differences in recanalization and outcomes as well as safety of DAPT and AC in the setting of AIS post MT with stenting when compared to patients without AC. Methods A retrospective search at a large comprehensive stroke center was conducted and data was analyzed from 2013 to 2022. Patients presenting with AIS on AC who had MT and required IC/EC stent were selected and compared to patients not on AC. Outcomes were measured as symptomatic ICH and mortality. Patient demographics, stroke risk factors and stroke severity were abstracted amongst other variables. Results There were 301 patients out of 917 (42.9% Female) who presented with anticoagulation use prior to mechanical thrombectomy requiring ic/ec stent placement and DAPT therapy. See Table 1 for baseline demographics. Symptomatic ICH was seen in 24 (7.9%) compared to 50 (8.1%), Odds ratio 0.86/ p‐value = 0.573, Mortality was seen in 51 (16.9%) patients who received DAPT and a/c compared to 129 (20.9%) (OR 0.67) p = 0.028. Logistic regression model did not show any significant difference (See Table 2). Conclusions There was no statistical difference in symptomatic ICH in acute ischemic stroke patients treated with mechanical thrombectomy and acute stenting on anticoagulation when compared to those without anticoagulation. There was statistical difference in mortality and DAPT/AC actually had lower mortality rates. This data suggests that performing intracranial and extracranial stenting in the acute stroke setting while on anticoagulation and adding DAPT is safe. A larger multicenter study with longer follow up is needed to further confirm these findings.